Use of Microfluidic Assays to Develop Reliable and Economic Nucleic Acid Application Technologies, Employing MicroRNAs for the Diagnostic Screening of Colon Cancer in Human Stool in Low-Resource Settings - Farid, E. Ahmed; Mostafa, Gouda; Nancy, C. Ahmed (International Journal of Nutrition, 2020)
Isolation methods that employ readily-available inexpensive supplies on the open market, which are reliable, as well as economical, such as nucleic acid amplification techniques (NAAT) based on microfluidic technology in low-resource research settings (LRRS) that meets the ASSURED guidelines are essential to develop a noninvasive diagnostic colon cancer screen in stool using micro(mi)RNA molecules. A combination of a microfluidic-based MiRNA stool test with a reliable rolling circle amplification/detection method applied to the quantification of miRNA molecules, result in an affordable sensitive and specific isothermal method for the noninvasive quantitative detection of miRNAs in LRRS. Scientists and engineers have become interested in miRNAs, and they have intensified their efforts to apply emerging simple detection tools to the important bioanalytical challenge of quantifying these small 18-26 nt long molecules. Some of the proposed approaches incorporate novel material, such as simple centrifuges and methods based on microfluidic technology, while others utilize the interesting biological properties of these molecules, such as forming branched RCA structures, allowing for the detection of these biomarker molecules at an attomolar "aM" concentration level, using low cost extraction and isothermal amplification methods in LRRS. We have been interested in studying colorectal cancer (CRC) because it is the 3rd most common malignancy worldwide, and stool can be obtained noninvasively from the patients. We have focused in this research on colon cancer (CC) because it is more common in the USA than rectal cancer (RC). The innovation of our approach lies in the exploratory use of an affordable, quantitative miRNA profiling in noninvasive stool samples in LRRS, whose extracted fragile total RNA is stabilized shortly after excretion from stool by commercially available kits, so it does not ever fragment, followed by quantitative standardized analytical tests that are neither labor intensive, nor require expensive instrumentation, in order to develop apanel of novel miRNA genes for the noninvasive diagnostic screening of early left and right sporadic colon cancers, more economically, and with higher sensitivity and specificity than any other colon cancer screening test currently available on the market. To show the clinical sensitivity and specificity of the proposed quantitative miRNA test using simple methodologies in LRRS,the miRNA results are to be correlated with FOBT, colonoscopy, and pathology data. Standardization establishes test’s performance criteria (sample selection, optimal sample running conditions, preservation and storage), in order to ensure that the assay will perform the same way in any laboratory, by any trained personnel, anywhere in low-resource laboratory settings worldwide.
Keywords: colon cancer; colonocytes; diagnosis; epidemiology; LRRS; magnetic beads; miRNAs